IMPLEMENTASI KERJASAMA REGIONAL PLAN OF ACTION IN COMBATING ILLEGAL, UNREPORTED, UNREGULATED FISHING (RPOA-IUU) DI ASIA TENGGARA : Studi Kasus IUU FISHING Di Laut Natuna Utara Indonesia Tahun 2015-2020 - Muhamad Rayada (2022)
The Indonesian Seas are blessed with many diversity and richness of wildlife and resources, one of the richest of them all is the Natuna Sea, which is also the northern-most point of Indonesia. Its location makes it prone to many illegal activities done by countries who shares border with the Exclusive Economic Zone, one of the most common crime is Illegal, Unreported, Unregulated Fishing (IUU Fishing). This IUU Fishing practices are often occurred in an island country such as Indonesia. This practice brings many harm and loss in Economic, Political, and Social sectors, in which this practice brings forth threat to the sovereignty and the securitization of the country. With considerations, Indonesia and a few other countries decided to create a regional regime which is known as Regional Plan of Action in Combating Illegal, Unreported, Unregulated Fishing (RPOA-IUU). This RPOA aims to raise awareness between member countries to respect each other's sovereign territory, promote responsible fishing and also combating IUU Fishing practice in the region. The purpose of this study is to report the development of the regime and also to find out regarding the implementation of the regime. The author will use 3 frameworks of thoughts which consist of Maritime Security, Illegal, Unreported, Unregulated Fishing, and lastly Regional Regime. In this study, the author uses a qualitative, describtive method in order to explain the issue thoroughly. The main data source will be collected through literature studies, The of this study states that although the implementation of RPOA-IUU is getting better by the year, is is by no means could be viewed as optimal. It is mainly caused by the implementation gap that is still found in the RPOA regime.